2007
DOI: 10.1002/anie.200602136
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Molybdenum Sulfide Fullerenes

Abstract: Opening the window: Hollow multilayer nano‐octahedra (see TEM image and structure) often appear in the laser‐ablation products of layered transition‐metal chalcogenides. Calculations on MoS2 nanoparticles demonstrate that nano‐octahedra exist in a window of stability between nanoplatelets and spherical fullerene‐like nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 21 publications
4
85
0
Order By: Relevance
“…To calculate the structure of larger nanooctahedra a phenomenological model based on the DFTB-MD method was developed. Further details on the calculation and construction principles are given in references (15,16). The multislice iteration and the electron optical imaging were calculated using EMS image simulation software (24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate the structure of larger nanooctahedra a phenomenological model based on the DFTB-MD method was developed. Further details on the calculation and construction principles are given in references (15,16). The multislice iteration and the electron optical imaging were calculated using EMS image simulation software (24).…”
Section: Methodsmentioning
confidence: 99%
“…In analogy to carbon fullerenes, and to the BN system, closed inorganic cages produced by energetic techniques are also expected to be highly symmetric and to occur in a specific size range (13). In a previous study, density functional tight binding calculations (DFTB) proceeded by molecular dynamics (MD) annealing were used to elucidate the structure and electronic properties of octahedral MoS 2 fullerenes (15,16). These octahedral particles manifest the strong relation between shape and properties, even among structures of the same size and composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method have been already successfully applied for numerous studies of chalcogenide nanostructures [10][11][12][13]. The tight-binding parameters (SlaterKoster tables) were evaluated to reproduce the structural and electronic properties of the bulk compound ReS 2 [24].…”
Section: Originalmentioning
confidence: 99%
“…These nanostructures were proposed first in [13,14] and realized in [15,16]. Indeed, MoS 2 nanooctahedra/nanotetrahedra were obtained by rapid quenching of laser- [15][16][17][18] or solar- [19] ablated MoS 2 soot or by an arc-discharge process [20]. It can, therefore, be concluded that highly exergonic reaction conditions and rapid quenching of the nanoclusters can access (meta-) stability windows, which favor new nanotubes that are not reachable by the conventional thermally-driven synthesis at <1000 °C.…”
Section: Introductionmentioning
confidence: 99%